Fluid overload due to intravenous fluid therapy for vaso‐occlusive crisis in sickle cell disease: incidence and risk factors. (15th July 2021) - Gaartman, Aafke E.; Sayedi, Ajab K.; Gerritsma, Jorn J.; de Back, Tim R.; van Tuijn, Charlotte F.; Tang, Man Wai; Heijboer, Harriët; de Heer, Koen; Biemond, Bart J.; Nur, Erfan
Summary: Intravenous fluid therapy (IV‐FT) is routinely used in the treatment of vaso‐occlusive crises (VOCs), as dehydration possibly promotes and sustains erythrocyte sickling. Patients with sickle cell disease (SCD) are at risk of developing diastolic dysfunction and fluid overload due to IV‐FT. However, data on the adverse effects of IV‐FT for VOC is sparse. We aimed to evaluate the incidence and risk factors of fluid overload due to IV‐FT in patients with SCD. Consecutive hospitalisations for VOC treated with IV‐FT between September 2016 and September 2018 were retrospectively analysed. The median (interquartile range) age was 25·0 (18·3–33·8) years and 65% had a severe genotype (HbSS/HbSβ 0 ‐thal). Fluid overload occurred in 21% of 100 patients. Hospital stay was longer in patients with fluid overload (6·0 vs. 4·0 days, P = 0·037). A positive history of fluid overload ( P = 0·017), lactate dehydrogenase level ( P = 0·011), and top‐up transfusion during admission ( P = 0·005) were independently associated with fluid overload occurrence. IV‐FT was not reduced in 86% of patients despite a previous history of fluid overload. Fluid overload is frequently encountered during IV‐FT for VOC. IV‐FT is often not adjusted despite a positive history of fluid overload or when top‐up transfusion is indicated, emphasising the need for more awareness of this complication and a personalised approach.